Beyond the mirror: an action-based model of knowing through reflection - Allen, Jedediah W. P.; Mirski, Robert; Bickhard, Mark H. (Frontiers in Developmental Psychology, 2024)
Epistemic reflection involves the creation of qualitatively new knowledge. Different models have been proposed to account for new knowing through reflection that have typically been grounded in an information-processing framework. However, there are in-principle arguments that information-processing approaches preclude the emergence of new representation altogether. Accordingly, any information-processing account of knowing through reflection is plagued by emergence issues. After discussing some of these emergence issues for four prominent models in the cognitive science literature, an alternative action-based model of representation and reflection is presented called interactivism. Interactivism’s model of representation, as grounded in action anticipations, serves as the foundational emergence needed to account for subsequent knowing through reflection. After introducing the interactivist models of representation and reflection through knowing levels, some of the implications for consciousness, enculturation, language, and developmental methodology are discussed.